Interactive Method in Duolingo Application: Improving Students' Arabic Listening Skills: Metode Interaktif dalam Aplikasi Duolingo: Meningkatkan Kemampuan Mendengar Bahasa Arab Siswa - Djafar, Zulvinawati; Liputo, Mohamad Rian; Adam, Muhamad Zikran (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Arabic has an important role in Islamic education in Indonesia, but students often experience difficulties in Arabic listening skills in the aspect of mastering the material. Purpose: This study aims to analyze the effect of interactive methods in the Duolingo application on students’ Arabic listening skills at MA Muhammadiyah Gorontalo. Method: This research design is quasi-experimental with a pretest-posttest approach. The study involved 40 students of grade XI as samples, who were divided into experimental and control groups. The instruments used included a listening ability test and a questionnaire to collect data on students’ perceptions. The research procedure included a pretest, an intervention using the Duolingo app for 4 weeks, and a posttest to analyze students’ listening ability improvement. Data were analyzed using descriptive and inferential statistics. Results and Discussion: The results showed that the use of interactive methods through the Duolingo application significantly improved students' listening skills at MA Muhammadiyah Gorontalo. In the experimental class, the average student pre-test score was 57.00, which increased to 76.40 in the post-test, resulting in a percentage increase of about 34.04%. Meanwhile, the control class that used the traditional method also improved, with an average pre-test score of 46.60 and a post-test of 61.00, recording an increase of about 30.92%. Although both groups showed progress, the experimental class showed greater improvement, indicating that the interactive method was more effective in improving Arabic listening skills compared to the conventional approach. Conclusions and Implications: The conclusion of this study shows that the interactive method in Duolingo is not only effective in improving students' listening skills, but also increases their motivation and engagement in learning Arabic. These results have important implications for Arabic language education curriculum development, encouraging teachers to integrate interactive learning technologies in the teaching process. This research also recommends further studies to explore the use of other applications in the context of language learning and their potential to improve language skills among students. As for some indicators that students must achieve include: (1) Understand Context (2) capture the main idea (3) analyze and evaluate.